2014
DOI: 10.1111/bjd.13355
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guidelines for laboratory screening for infectious diseases before initiation of systemic immunosuppressive agents in patients with autoimmune bullous dermatoses

Abstract: Autoimmune bullous dermatoses (ABD) compromise the skin's innate barrier function for preventing infection. Treating patients with ABD frequently requires systemic immunosuppressive therapy, often with multiple agents. Currently, no pretreatment infection testing guidelines are available for clinicians caring for patients with ABD. We performed a systematic literature review in other medical disciplines that use similar iatrogenic immunosuppressive medications to treat various diseases and conditions and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 68 publications
1
19
0
1
Order By: Relevance
“…A recent evidence-based guideline on the screening for infectious diseases in patients with autoimmune bullous dermatoses, recommends testing patients for Mycobacterium tuberculosis , and hepatitis B and C viruses, before prescribing rituximab treatment 14. On the other hand, doctors must educate their patients to avoid colonization and infection of their skin (proper hand washing, nail cleaning, and avoiding any physical contact with other patients) and recognize early signs and symptoms of infection to seek health assistance for rapid diagnosis and treatment 36.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evidence-based guideline on the screening for infectious diseases in patients with autoimmune bullous dermatoses, recommends testing patients for Mycobacterium tuberculosis , and hepatitis B and C viruses, before prescribing rituximab treatment 14. On the other hand, doctors must educate their patients to avoid colonization and infection of their skin (proper hand washing, nail cleaning, and avoiding any physical contact with other patients) and recognize early signs and symptoms of infection to seek health assistance for rapid diagnosis and treatment 36.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Keith et al . from the Mayo Clinic have provided a systematic review of all the guidelines related to particular infection risks with each immunosuppressive treatment and have concluded the review with a useful table of suggested screening.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Thus far, there are no internationally agreed vaccination protocols prior to initiating immunosuppressive therapies in AIBDs . However, in this review, varicella zoster vaccination is recommended before treatment, where possible …”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…There are few guidelines for the screening of infectious diseases before the initiation of immunosuppressive treatments for skin disorders . The medical board of the National Psoriasis Foundation in the USA recommends that psoriatic patients be screened for HBV infection before immunosuppressive medications are administrated .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] There are few guidelines for the screening of infectious diseases before the initiation of immunosuppressive treatments for skin disorders. [12][13][14] The medical board of the National Psoriasis Foundation in the USA recommends that psoriatic patients be screened for HBV infection before immunosuppressive medications are administrated. 14 For patients with AIBD, testing for HBV, hepatitis C virus (HCV) and M. tuberculosis infections is recommended before treatment containing rituximab is initiated.…”
Section: Introductionmentioning
confidence: 99%